The development of syntactic complexity in university students’ essays - Istiharoh, Agus Ferani; Pranowo, Dwiyanto Djoko (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
This research aimed to describe quantitatively the development of students’ syntactical complexity during the Essay Writing Course measured with the L2SCA tool by Lu. The research basically implemented a descriptive-quantitative research design. The primary data were collected from 20 students majoring in Agribusiness and taking an essay writing course in Yogyakarta Muhammadiyah University (UMY) during one semester from February to July 2022 in a researcher class. They wrote three essays gradually from one session to the third session of the class. The essays were analyzed quantitatively using the L2SCA tool by following the indices of the tools as the reference to see the students’ syntactical complexity. In addition, the participants wrote three essays divided into three times writing tests. Overall, the analysis method was conducted by following a systematic procedure; classifying, scoring, displaying, describing, interpreting, discussing, and concluding. As a result, this study reveals that syntactical development of students’ essays during a semester session of writing course fluctuated from the first writing until the third writing. Although along the writing supervision, they had consultation sessions, the result did not show gradual and constant progress. It implied that the students’ acquisition of syntactical complexity represented in writing did not improve progressively in all syntactical indices. However, among the three essays the participants wrote, they excel most in second essay or argumentative essay. Further, it is necessary to relate the essay’s genre to the result of students’ writing for each of the essays has a special characteristic and level of difficulty.